A Randomized Study of Interferon α‐2b Versus No Treatment as Consolidation After High Dose Therapy and Autologous Stem Cell Transplantation for Patients With Relapsed Lymphoma. (8th October 2013) - Bosly, André; Grigg, Andrew; Holte, Harald; Gisselbrecht, Christian; Radford, John; Rossi, Andrea; Lopez‐Guillermo, Armando; Trneny, Marek; Sebban, Catherine; Hagberg, Hans; Leal da Costa, Fernando; Colombat, Philippe; et al.
Abstract : Background: Patients with lymphoma who have experienced a first relapse or progression and have disease deemed sensitive to salvage chemotherapy nevertheless have a high likelihood of having a second relapse. To decrease the likelihood of a second relapse after high‐dose therapy (HDT) and autologous stem cell transplantation (ASCT), interferon (IFN) α‐2b was given in a prospective randomized international trial. Methods: In this trial, 221 patients with varying histologic diagnoses (8 small lymphocytic, 37 follicular, 9 mantle, 90 diffuse large B‐cell, 20 peripheral T‐cell, 3 high‐grade B‐cell non‐Hodgkin lymphoma, and 54 Hodgkin lymphoma) were randomly assigned to receive no further treatment (arm A: 117 patients) or IFNα‐2b, 3 MU three times weekly, for 18 months (arm B: 104 patients). Results: In arm B, 21 patients (20%) did not receive IFNα‐2b because of early progression or absence of hematologic recovery, 29 patients (28%) completed the 18 months of treatment, and 54 patients (52%) interrupted treatment because of progression (23%) or toxicity (29%). Event‐free survival and overall survival were not different between the two arms on an intent‐to‐treat analysis and also if analysis was restricted to patients who were alive and had not experienced disease progression three months after transplantation. The study was not sufficiently powered to evaluate effects in histologic subtypes. Conclusion: In this trial, post‐autograft IFNα‐2b did not improve outcomes in a heterogeneous group of patients with lymphoma. Abstract : 摘要 背景 . 经历过第1次复发或疾病进展以及被认为对挽救性化疗敏感的淋巴瘤患者第2次复发的几率很高。一项前瞻性随机化国际性试验使用干扰素（IFN）α‐2b治疗，以期降低大剂量治疗（HDT）和自体干细胞移植（ASCT）后第2次复发的几率。 方法 . 试验中，221例确诊为不同组织学类型（8例小淋巴细胞型，37例滤泡型，9套细胞型，90例弥漫大B细胞型，20例外周T细胞型，3例高级别B细胞型非霍奇金淋巴瘤，以及54例霍奇金淋巴瘤）的患者随机分为不予进一步治疗组（组A：117例患者）或IFN α‐2b组（组B：104例患者），3 MU每周3次，持续至18个月。 结果 . 组B中，21例患者（20%）因早期疾病进展或未获得血液学缓解而未接受IFN α‐2b，29例（28%）完成了18个月治疗，54例（52%）因疾病进展（23%）或毒性反应（29%）而中断治疗。意向治疗分析显示，两组无事件生存率和总生存率无差异，如果分析仅限于移植后3个月未出现疾病进展的仍生存患者，结果仍无差异。研究的检验效能不足以评估组织学亚型的影响。 结论 . 本试验中，移植后使用IFN α‐2b并未改善淋巴瘤异质性人群的生存结果。 The Oncologist 2013;18:1189